2020
DOI: 10.1111/jam.14588
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of inflammatory response and gut microbiota in ankylosing spondylitis mouse model by bioactive peptide IQW

Abstract: Aims Ankylosing spondylitis (AS) is a widespread and chronic inflammatory autoimmune disease of unknown provenance. Naturally occurring peptides and proteins have shown significant promise as modulators of immune responses. Thus, the aims of this study were to assess the protective effects of the bioactive peptide IQW (Ile‐Gln‐Trp) with respect to inflammatory indicators, gut microbiota and oxidative stress, and to examine the potential mechanisms of these effects. Methods and Results A mouse model was prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…We found that Bacteroides, Akkermansia, and Verrucomicrobia were increased in zymosan injected mice. Our study was consistent well with other recent studies showing that Akkermansia, Bacteroides , and Verrucomicrobia were significantly increased in proteoglycan induced AS mouse model 32 . We found that Oscillospira was significantly increased in E2 or Laso treated mice.…”
Section: Discussionsupporting
confidence: 94%
“…We found that Bacteroides, Akkermansia, and Verrucomicrobia were increased in zymosan injected mice. Our study was consistent well with other recent studies showing that Akkermansia, Bacteroides , and Verrucomicrobia were significantly increased in proteoglycan induced AS mouse model 32 . We found that Oscillospira was significantly increased in E2 or Laso treated mice.…”
Section: Discussionsupporting
confidence: 94%
“…We found that Bacteroides, Akkermansia, and Verrucomicrobia were increased in zymosan injected mice. Our study was consistent well with other recent studies showing that Akkermansia, Bacteroides, and Verrucomicrobia were signi cantly increased in proteoglycan induced AS mouse model [33]. We found that Oscillospira was signi cantly increased in E2 or Laso treated mice.…”
Section: Discussionsupporting
confidence: 93%
“…FastQC 1 (v. 0.11.3) was initially utilized for quality control (QC) assessment of RNA-seq reads, after which rRNA reads, adapter sequences, and low-quality reads were trimmed with the seqtk 2 software. BWA-MEM (v2.0.4) was then used to map the trimmed reads to the human reference genome (hg38), after which CIRI was used to predict lncRNAs in these RNA-seq data, and SRPBM was used to quantify lncRNA counts therein.…”
Section: Discussionmentioning
confidence: 99%